The problems of the formation of health life: legal aspects - Lukjanchenko M.I (Kharkov National Pedagogical University, 2011)
In the article the problems of the formation and promotion of health life have been analyzed, the main trends of the activity which concerns to the formation of health life according to the legal documents have been revealed. On the basis of the analysis of WHO charters and Ukrainian legislative base the common and different treats have been pointed out. It is defined the sources of the problem of healthy lifystyle according legal documents.